2012
DOI: 10.1007/s11901-011-0121-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute HCV: Will IL28B Testing Change the Paradigm?

Abstract: HCV infection will spontaneously resolve in 30% to 50% of patients. Patients with beneficial IL28B genotypes are more likely to clear spontaneously, while other are unlikely to, with less than 15% clearance rate. These patients would therefore be very likely to benefit from immediate treatment with pegylated interferon. In delayed treatment, ribavirin might be required to achieve similar results, making the delayed treatment also from the cost perspective only attractive in those likely to clear spontaneously:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These studies found a >50% spontaneous clearance rate in patients with a favorable IL28B genotype. This high spontaneous clearance rate suggests that IL28B can be helpful in individualizing treatment for patients with clinically evident acute hepatitis C [50]. Patients with an IL28B genotype (i.e., rs12979860 CC) that is more responsive to interferon, especially in the presence of jaundice, have a more than 50% chance of spontaneous viral clearance and can defer treatment as they are likely to respond to interferon-based therapy even if treatment is initiated at a later time point.…”
Section: Can Il28b Change the Approach To Early Versus Delayed Treatmmentioning
confidence: 99%
“…These studies found a >50% spontaneous clearance rate in patients with a favorable IL28B genotype. This high spontaneous clearance rate suggests that IL28B can be helpful in individualizing treatment for patients with clinically evident acute hepatitis C [50]. Patients with an IL28B genotype (i.e., rs12979860 CC) that is more responsive to interferon, especially in the presence of jaundice, have a more than 50% chance of spontaneous viral clearance and can defer treatment as they are likely to respond to interferon-based therapy even if treatment is initiated at a later time point.…”
Section: Can Il28b Change the Approach To Early Versus Delayed Treatmmentioning
confidence: 99%